Primary tumor regression patterns in esophageal squamous cell cancer treated with definitive chemoradiotherapy and implications for surveillance schemes - Chen M; Liu P; Chen Y; Chen Z; Shen M; Liu X; Li X; Lin Y; Yang R; Ni W; Zhou X; Zhang L; et al. (Cancer Management and Research, 2019)
Mingqiu Chen,1–4 Pingping Liu,5 Yuangui Chen,6 Zhiwei Chen,7 Minmin Shen,5 Xiaohong Liu,5 Xiqing Li,5 Yu Lin,1 Rongqiang Yang,8 Wei Ni,8 Xin Zhou,8 Lurong Zhang,1 Ye Tian,3,4 Junqiang Chen11Department of Radiation Oncology, Fujian Cancer Hospital & Fujian Medical University Cancer Hospital, Fuzhou, Fujian, China; 2Fujian Provincial Platform for Medical Laboratory Research of First Affiliated Hospital, Fujian, China; 3The Second Affiliated Hospital of Soochow University, Jiangsu, China; 4Institute of Radiotherapy & Oncology, Soochow University, Jiangsu, China; 5Fujian Medical University Cancer Hospital, Fujian, China; 6Department of Radiation Oncology, Fujian Medical University Union Hospital, Fujian, China; 7Fuzhou Center for Disease Control and Prevention, Fuzhou, Fujian, China; 8Cancer and Genetics Research Complex, Department Molecular Genetics and Microbiology, College Medicine, University of Florida, Gainesville, FL, USAPurpose: The primary tumor regression patterns of patients with esophageal squamous cell carcinoma (ESCC) treated with definitive chemoradiotherapy (CRT) were investigated to determine an optimal surveillance scheme.Method: The clinical data and radiology images of patients before CRT, at completion of CRT and every 1–3 months for the subsequent 12 months or until disease progression were retrospectively reviewed to define the patterns of primary tumor regression after CRT. Survival rates were analyzed statistically in order to determine an optimal surveillance scheme.Results: A total of 82 patients were enrolled in the present study for analysis. At the first surveillance visit date at the end of CRT, a total of 21 patients achieved complete response (early-CR), 29 patients reached incomplete response (IR), 25 patients maintained stable disease (SD) and 7 patients encountered progression of disease (PD). During subsequent surveillance, a total of 14 IR patients regressed continuously to CR (later-CR), 15 patients maintained IR (early-IR) and 9 SD patients gradually regressed to IR (later-IR). At full tumor regression (FTR), a total of 21, 14, 15, 9, 16 and 7 patients were defined as early-CR, later-CR, early-IR, later-IR, SD and PD, respectively. The median FTR time for later-CR and later-IR was 7.5 and 7 weeks, respectively. The 3-year overall survival rate of the early-CR group was 85.7% (P<0.001), which was higher compared with the later-CR (16.7%), early-IR (20%), later-IR (11.1%), SD (6.3%) and PD (0%) groups.Conclusion: The early-CR following CRT is a robust prognostic predictor in patients with ESCC. To optimize the determination of tumor regression, ≥7 weeks after CRT is an optimal initial surveillance visit date. The surveillance of non-CR patients should concentrate on symptoms, nutrition and psychosocial support, rather than screening for recurrence of the disease.Keywords: concurrent chemoradiotherapy, esophageal squamous cell carcinoma, surveillance, survival, tumor regression